Introduction to statistics and data analysis - Peck, Roxy; Olsen, Chris; Devore, Jay L. (CENGAGE Learning, 2012)
This book guides students through an intuition-based learning process that stresses interpretation and communication of statistical information. It includes coverage of the graphing calculator as well as expanded coverage of probability.